SISTEM INFORMASI PRAKTEK KERJA INDUSTRI BERBASIS WEB DI SMKN 1 CIKANDE - Nur Hidayanti; Rizki Fatullah; Nur Huda (LPPM Unbaja, 2022)
In the Industrial Job Training system that is currently running in SMK, there are still obstacles such as the registration process, filling out journal books and the student assessment process for Industrial Work Practices. With a web-based industrial work practice information system can provide information about industrial work practice programs online. This system has advantages in terms of speed of presentation of the resulting information, in addition to being web-based, this system can be accessed at an unspecified time and place. The purpose of this study is to design an administrative information system that can provide information related to the process of industrial work practices at SMKN 1 Cikande. By using a website and the PHP programming language, this information system can be used anytime and anywhere. The Waterfall method is a method that implements design by working with users. By using the Waterfall Method, the system can be designed according to the needs and desires of the user. The design results show that the system can record the registration process and ongoing industrial work practice guidance, both to students and supervisors who use it. This design is very useful for the administration and vice principal in providing information and integrating the results of industrial work practices at SMKN 1 Cikande.